Kochland : [compact disc, unabridged] the secret history of Koch Industries and corporate power in America - Leonard, Christopher, 1975- (Simon & Schuster Audio, 2019)
Christopher Leonard uses the extraordinary account of how one of the biggest private companies in the world grew to be that big to tell the story of modern corporate America.